PERENCANAAN PAKET WISATA SPIRITUAL DI KAWASAN TAMAN NASIONAL GUNUNG RINJANI - Deya Pradnyana, I Komang; Sendra, I Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
Rinjani Mountain area has some potential physical and non-physical is very unique as lakes, caves, and many others. In connection with the potential for physical and non-physical possessed the area of Mount Rinjani, in this study raised a variety of issues that can be used as a spiritual travel package including : (1) What are the potential physical and non-physical-owned area of Mount Rinjani, West Nusa Tenggara. (2) How to plan a spiritual tour packages in the area of Mount Rinjani, West Nusa Tenggara. This study was conducted to determine the physical and non-physical potential contained in the area of Mount Rinjani, then packed into a spiritual tour packages. Data collection techniques used through observation, interviews, documentation and literature.Data analysis techniques used in this research is qualitative descriptive analysis. Results from this research that the area of Mount Rinjani has eleven potential that can be packed into three spiritual package.(a) Spiritual packages Senanga Danau Segara Anak,(b) Spiritual Package Senaru Pancor Emas,(c) Spiritual package Sembalun Puncak Rinjani.
Keywords: Potential Travel, Spiritual, Travel Package